Work Environment, Work Practices, and Employee Work Discipline on Employee Performance in the Hospitality Industry: Lingkungan Kerja, Praktik Kerja, dan Disiplin Kerja Karyawan Terhadap Kinerja Karyawan pada Industri Perhotelan - Ulumudin, Muhamad Ihya; Sari, Herlinda Maya Kumala (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the influence of the work environment, work practices, and employee work discipline on employee performance in the hospitality industry (Case Study: Hotel Utami Juanda). The method used in this research is a quantitative approach. Sampling in this study was conducted by saturated sampling method, with the number of respondents as many as 52 respondents, employees of Hotel Utami Juanda. The data analysis technique used in this study used the SPSS version 24 program.The results of this study prove that the work environment does not partially affect the performance of Utami Juanda Hotel employees, work practices have a partially significant effect on the performance of Utami Juanda Hotel employees, employee work discipline has a partially significant effect on the performance of Utami Juanda Hotel employees and the work environment, practice Work, and Employee Discipline have a simultaneous effect on Employee Performance in the Hospitality Industry (Case Study: Hotel Utami Juanda).